2018
DOI: 10.1002/asia.201800759
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Pincer‐Catalyzed Hydrogenation of Lactams to Amino Alcohols

Abstract: By using the commercially available ruthenium pincer complex (Ru-MACHO-BH) as a catalyst, the challenging direct hydrogenation of lactams and analogues has been successfully accomplished to deliver corresponding value-added amino alcohols in good-to-excellent yields under mild reaction conditions. Remarkably, in addition to N-protected lactams, unprotected ones could also be readily reduced in the presence of a catalytic amount of weak base or even under neutral reaction conditions, which further highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…In the methanol cycle, the hydrogenation of hemiaminal to methanol is rather straightforward as also shown in the hydrogenation of carbamate and urea derivatives by Ru-MACHO and similar pincer complexes. 53,[124][125][126][127][128][129][130][131] Scheme 4 shows two key resting state complexes A and B. The formation of metal-formate complex A via metal-hydride transfer to CO 2 followed by rearrangement in II with a small energy barrier is thermodynamically favored due to both metaloxygen bonding and N-HÁ Á ÁO hydrogen bonding interactions.…”
Section: Metal/nh Bifunctional Molecular Catalystsmentioning
confidence: 99%
“…In the methanol cycle, the hydrogenation of hemiaminal to methanol is rather straightforward as also shown in the hydrogenation of carbamate and urea derivatives by Ru-MACHO and similar pincer complexes. 53,[124][125][126][127][128][129][130][131] Scheme 4 shows two key resting state complexes A and B. The formation of metal-formate complex A via metal-hydride transfer to CO 2 followed by rearrangement in II with a small energy barrier is thermodynamically favored due to both metaloxygen bonding and N-HÁ Á ÁO hydrogen bonding interactions.…”
Section: Metal/nh Bifunctional Molecular Catalystsmentioning
confidence: 99%
“…Both complexes present a Ru-BH 4 moiety, being able to deliver the active catalyst at the reaction conditions. In 2018, Tu et al 46 showed that the commercially available [Ru-MACHO-BH] complex is an active catalyst for the synthesis of protected and unprotected amino alcohols by deaminative hydrogenation of lactams employing catalytic amounts of K 3 PO 4 ( Fig. 2B9).…”
Section: Development Of Homogeneous Catalystsmentioning
confidence: 99%
“…Finally, full reduction of pyrrolidones and caprolactams to the corresponding amino alcohols has been accomplished by catalytic hydrogenation (425)(426)(427) and by reduction with sodium borohydride (428)(429)(430)(431) and samarium iodide (432) (Scheme 23).…”
Section: Reduction Of Pyrrolidones and Caprolactamsmentioning
confidence: 99%
“…Scheme 23Hydrogenation and reduction of pyrrolidones and caprolactams to N-substituted amino alcohols(427,428).…”
mentioning
confidence: 99%